Edukasi Masyarakat Dalam Mencegah Komplikasi Hipertensi dengan Metode DAGUSIBU Obat-Obat Anti Hipertensi - Putri, Anggy Utama; Rosadi, Erik (Yayasan Daarul Huda Kruengmane, 2024)
Blood pressure that is higher than normal or ?140/90 mmHg is called hypertension, a condition of the circulatory system. Apart from that, DAGUSIBU is also an effort to improve public health through health service activities by pharmaceutical personnel. This community service activity aims to provide education about preventing hypertension complications using the DAGUSIBU method, Plaju Darat sub-district, Palembang city. The method of implementing the activity is in the form of education consisting of counseling, discussion and question and answer. Participants in educational activities are the Plaju Darat sub-district community, Palembang City. The material presented is counseling on preventing hypertension complications using the DAGUSIBU method (GET, USE, SAVE and DISPOSE) of medication. This community service activity succeeded in increasing the participants' knowledge and understanding of Hypertension and DAGUSIBU, there was an increase in knowledge. This can support the realization of government programs to improve health services for the community